Síntese, caracterização e atividade fotocatalítica de catalisadores nanoestruturados de TiO2 dopados com metais - William Leonardo da Silva; Marla Azário Lansarin; Celso Camilo Moro (Química Nova, 2013)
Titanium dioxide nanostructured catalysts (nanotubes) doped with different metals (silver, gold, copper, palladium and zinc) were synthesized by the hydrothermal method in order to promote an increase in their photocatalytic activity under visible light. The catalysts were characterized by X-ray diffraction, diffuse reflectance spectroscopy, transmission electron microscopy and specific area and pore volume determination. The materials' photocatalytic activity was evaluated by rhodamine B decomposition in a glass batch reactor. Under UV radiation, only nanotubes doped with palladium were more active than the TiO2 P25, but the samples doped with silver, palladium and gold exhibited better results than the undoped samples under visible light.